2017
DOI: 10.1111/acem.13061
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Use for Adults With Head Injury: Describing Likely Avoidable Emergency Department Imaging Based on the Canadian CT Head Rule

Abstract: Background: Millions of head computed tomography (CT) scans are ordered annually, but the extent of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 32 publications
(39 reference statements)
4
49
1
3
Order By: Relevance
“…It is also promising that the modest reductions in CT use observed here in community settings were similar to those observed at academic-based Level I trauma centers. 8,9,11,23,24 However, our findings differ from those of a similar study of Canadian CT Head Rule implementation in Canada, which found a negative or null effect on CT use. 10 This may be a result of differences in the patient populations, medical cultures, physician training, or other variation between US and Canadian health care systems.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…It is also promising that the modest reductions in CT use observed here in community settings were similar to those observed at academic-based Level I trauma centers. 8,9,11,23,24 However, our findings differ from those of a similar study of Canadian CT Head Rule implementation in Canada, which found a negative or null effect on CT use. 10 This may be a result of differences in the patient populations, medical cultures, physician training, or other variation between US and Canadian health care systems.…”
Section: Discussioncontrasting
confidence: 99%
“…8,9 Among studies reporting use of clinical decision rules, including the Canadian CT Head Rule, findings have been mixed. Some studies show no change, whereas others show increased imaging use 10 without eliminating unwarranted imaging or increasing diagnostic yield 5,11,12 despite expectations that Canadian CT Head Rule adherence will substantially decrease CT use.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As we discussed in our original article, we used a hybrid design in an attempt to capitalize on the strengths, and compensate for the limitations, inherent to each strategy. 3 We believe that our methodology allowed our findings to be reliably applied to a group of more than 27,000 encounters in community EDs; we trust readers to decide for themselves whether or not this adds value to the 100 included in our chart review or the referenced study of 346 encounters in an academic Level I trauma center. 1 Dr. Melnick also expresses concern about the lack of a power calculation in our study.…”
mentioning
confidence: 91%